P43 An integrated and sustainable education programme improves knowledge, leadership and confidence in acute non invasive ventilation (NIV) in line with the BTS quality standards. (12th November 2019) - Peal, CA; Moriarty, AD; Wyatt, J; Molyneux, AW; Smith, DP
Abstract : Introduction: Inspiring Change, the 2017 NCEPOD report on NIV demonstrated that improvement in clinical and/or organisational care was required in 73.2% of patients. Many hospitals (45.4%) did not maintain a record of competency for staff delivering acute NIV care. BTS Quality Standards state that staff initiating or making changes to acute NIV treatment must be competent and a register should be maintained. At Sherwood Forest Hospitals, we maintained a log of competency for Band 6 acute NIV nurses but did not record evidence of training for rotating doctors or ward nurses. Methods: We developed a multifaceted, multi-disciplinary, integrated and sustainable education programme for all staff with responsibility for managing acute NIV. This comprised an E-learning package; a low-fidelity (lo-fi), in-situ simulation training and quarterly update sessions referencing our BTS NIV QI toolkit Acute NIV prescription; and posters featuring a newly created treatment acronym: 'BREATHE'. Feedback from E-learning is electronically sought, and a register maintained through the package's final assessment. The simulation employed a 'Resusci Annie' manikin as patient, a side-room or treatment room on our acute NIV ward, and mock notes and drug card. Faculty comprised one facilitator and a respiratory specialist nurse. Junior doctors were trained in-hours during induction to the respiratory department. Pre- and post-simulation questionnaires, using a 5-point Likert scale, were completed and results analysed using a Wilcoxon signed-rank test. Results: 14 junior doctors undertook the lo-fi, in-situ simulation, and questionnaire responses demonstrated statistically significant (Table 1) improvements in knowledge, confidence, leadership and escalation. 32 staff, including 13 nurses and 19 junior doctors, completed the E-learning package within the first 2 months. Feedback was universally positive with all staff reporting that the knowledge gained will improve their work and the assessment consolidated their learning. Conclusion: Appropriate training and registration for all staff involved in acute NIV care is essential in line with BTS Quality Standards. The multidisciplinary in-situ simulation is reproducible and delivers similar outcomes to more formalised training in an expensive simulation centre. An E-learning programme is a sustainable method of integrating clinical documentation and assessments allowing a contemporaneous register of staff competency and training.